Drug sensitivity patterns of bacterial isolates from septic post-operative wounds in a regional referral hospital in Uganda - Anguzu, J. R.; Olila, D. (African health sciences, 2007)
Wound infections have been a problem in the field of surgery for a long time.Advances in control of infections have not completely eradicated this problem because of development of drug resistance.Antimicrobial resistance can increase complications and costs associated with procedures and treatment. A study was carried out on drug sensitivity patterns of bacterial isolates from septic postoperative wounds in Jinja hospital, Uganda.This study was designed to determine the distribution of bacterial pathogens isolated from septic post-operative wounds and their antimicrobial susceptibility patterns. Method: Specimens of pus swabs were collected aseptically and analysed in the laboratory. Colony characteristics and Grams technique were used to differentiate the organisms. Biochemical tests were done to confirm the species of the organisms. Sensitivity testing was done on the isolates using the disk diffusion method. Results: Pathogenic bacteria were recovered from 58.5% of the specimens.The isolates were: S.aureus (45.1%), Coliforms (16.9%), Proteus mirabilis (11.3%), P.aeruginosa (9.9%), Klebsiella pneumoniae (7.0%) and Enterobacter spp (2.82%). Most of the organisms were sensitive to gentamicin, ciprofloxacin and ceftazidime.There was resistance to ampicillin, amoxycillin and chloramphenicol. Staphylococcus aureus was generally sensitive to gentamicin (87.5%), ciprofloxacin (68.7%) and methicillin (75%), but resistant to erythromycin (56.2%) and ampicillin (97%). Most of the gram-negative bacteria isolated (Coliforms, P.aeruginosa , E.coli , Proteus mirabilis , and Klebsiella pneumoniae ) were sensitive to Ciprofloxacin, Gentamicin and Ceftazidime but resistant to Ampicillin,Amoxycillin and Chloramphenicol. Methicillin-resistant Staphylococcus aureus (MRSA) strains formed 25% of this species. Pseudomonas aeruginosa was sensitive to gentamicin (87.5%) and ceftazidime (85.7%) but showed resistance to ciprofloxacin (57.2%). Some organisms e.g. S.aureus, Pseudomonas aeruginosa and Proteus mirabilis exhibited multi-drug resistance to the antibiotics tested. Since a high proportion of samples had positive cultures, infection control is recommended as a strategy to minimise spread of resistant organisms. It is recommended that gentamicin, ciprofloxacin and ceftazidime be used in preference to ampicillin and amoxycillin for treatment of septic wounds. There is need to develop national surveillance of antibiotic- resistant organisms.
Keywords: Regional referral hospital; Drug sensitivity patterns; Septic post-operative wounds